2010
DOI: 10.1002/cne.22338
|View full text |Cite
|
Sign up to set email alerts
|

Visual deprivation increases accumulation of dense core vesicles in developing optic tectal synapses in Xenopus laevis

Abstract: Despite considerable progress in understanding the molecular components of synapses in the central nervous system, the ultrastructural rearrangements underlying synaptic development remain unclear. We used serial section transmission electron microscopy and three-dimensional reconstructions of the optic tectal neuropil of Xenopus laevis tadpoles to detect and quantify changes in synaptic ultrastructure over a 1-week period from stages 39 and 47, during which time the visual system of Xenopus tadpoles becomes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…In addition, we often observed that axonal boutons contacting extending dendrites, which had at most a 4h lifetime, contained dense core vesicles (Fig. 5M), consistent with the idea that they are involved in synaptogenesis (Li and Cline, 2010). As observed in the neuron imaged at daily intervals (Fig 2A), extending dendrites formed synapses with MSBs.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, we often observed that axonal boutons contacting extending dendrites, which had at most a 4h lifetime, contained dense core vesicles (Fig. 5M), consistent with the idea that they are involved in synaptogenesis (Li and Cline, 2010). As observed in the neuron imaged at daily intervals (Fig 2A), extending dendrites formed synapses with MSBs.…”
Section: Resultssupporting
confidence: 84%
“…We previously reported that the proportion of the presynaptic terminal area that is occupied by clustered synaptic vesicles increased during development when synapses mature, and termed this metric the maturation index (Li and Cline, 2010). Here, we mapped the maturation index of synapses on stable, extended and retracted branches (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From the presynaptic point of view, a prominent ultrastructural feature of synaptic maturation is the increase in the number of synaptic vesicles per terminal [21-23], which likely contributes to the increase in probability of transmitter release in mature synapses [17]. Transmission at immature glutamatergic synapses is mainly mediated by NMDA receptors, which shift their kinetics by replacing NMDA receptor subunit 2B-containing receptors with NMDA receptor subunit 2A-containing receptors [24,25].…”
Section: Synapse and Dendrite Developmentmentioning
confidence: 99%
“…To test whether synaptic contacts onto dnIR-expressing tectal neurons were changed in dnIR-expressing neurons, we used electron microscopy to estimate synapse density on tectal neurons. This methodology gives both definite identification of synaptic contacts onto transfected neurons and ultrastructural information about both pre- and post-synaptic profiles [23]. We estimated synapse density by measuring the number of green fluorescent protein (GFP)-labeled synapses normalized to the total area of GFP-labeled dendritic profiles and found that dnIR-expressing dendrites had less than half of the synapse density of GFP-labeled neuron controls, although no changes in other ultrastructural features or synapse maturation were observed (Figures 6A-C) [84].…”
Section: The Insulin Receptormentioning
confidence: 99%
“…These alterations include changes to connectivity (e.g. number of synapses) as well as modifications at the level of individual synapses (Aizenman and Cline, 2007; Li and Cline, 2010; Zhao et al, 2013). Hippocampal, neocortical and spinal neurons in culture exhibit ‘synaptic scaling’ where globally blocking activity leads to an increase in the amplitudes of miniature EPSCs and ionotropic glutamate receptor expression at excitatory synapses.…”
Section: Activity-mediated Modifications At Retinal Synapsesmentioning
confidence: 99%